Jihad and Islam in World War I : studies on the Ottoman Jihad at the centenary of Snouck Hurgronje's "Holy war made in Germany" - Zürcher, Erik Jan (Debates on Islam and society., 2016)
Today's headlines are full of references to jihad and jihadists, but they're nothing new: a century ago, the entry of the Ottoman Empire into World War I was accompanied by a loud proclamation of jihad as well. This book resurrects that largely forgotten aspect of the war, investigating the background and nature of the proclamation, as well as its effects in the wider Middle East, the fears it stoked among German and British military leaders, and the accompanying academic debates about holy war and Islam.